Cutting through the Jungle: Disambiguating Model-based Traceability Terminology - Holtmann, Jörg; Steghofer, Jan-Philipp; Rath, Michael; Schmelter, David (2020 IEEE 28th International Requirements Engineering Conference (RE))
Traceability, a classic requirements engineering topic, is increasingly used in the context of model-based engineering. However, researchers and practitioners lack a concise terminology to discuss aspects of requirements traceability in situations in which engineers heavily rely on models and model-based engineering. While others have previously surveyed the domain, no one has so far provided a clear, unambiguous set of terms that can be used to discuss traceability in such a context. We therefore set out to cut a path through the jungle of terminology for model-based traceability, ground it in established terminology from requirements engineering, and derive an unambiguous set of relevant terms. We also map the terminology used in existing primary and secondary studies to our taxonomy to show differences and commonalities. The contribution of this paper is thus a terminology for model-based traceability that allows requirements engineers and engineers working with models to unambiguously discuss their joint traceability efforts.

Scenario-based Specification of Security Protocols and Transformation to Security Model Checkers - Koch, Thorsten; Dziwok, Stefan; Holtmann, Jörg; Bodden, Eric (ACM/IEEE 23rd International Conference on Model Driven Engineering Languages and Systems (MODELS ’20))

Echtzeitfähige Planung optimierter Trajektorien für sensorgeführte, kinematisch redundante Mechanismen auf einer Industriesteuerung - Schütz, Stefan; Rüting, Arne Thorsten; Henke, Christian; Trächtler, Ansgar (Entwurf komplexer Automatisierungssysteme (EKA))

Language-agnostic Injection Detection - Hermerschmidt, Lars; Straub, Andreas; Piskachev, Goran (2020 IEEE Security and Privacy Workshops (SPW))

SWAN_ASSIST: Semi-Automated Detection of Code-Specific, Security-Relevant Methods - Piskachev, Goran; Nguyen Quang Do, Lisa; Johnson, Oshando; Bodden, Eric (2019 34th IEEE/ACM International Conference on Automated Software Engineering (ASE))

AuthCheck: Program-State Analysis for Access-Control Vulnerabilities - Piskachev, Goran; Petrasch, Tobias; Späth, Johannes; Bodden, Eric (Lecture Notes in Computer Science)

Softwareentwicklung wie am Fliessband - Koch, Thorsten; Meyer, Matthias; Fazal-Baqaie, Masud; Runschke, Hubert (Software Engineering 2020 (SE 2020))

Mechatronischer Entwurf eines geregelten Federungssystems für mittelschwere gepanzerte Kettenfahrzeuge - Gense, Alexander

Produkttolerante Automation zellenbasierter Fertigungssysteme - Bertelsmeier, Fabian

Microstructural investigation on phase transformation during flow forming of the metastable austenite AISI 304 - Rozo Vasquez, Julian; Arian, Bahman; Riepold, Markus; Homberg, Werner; Trächtler, Ansgar; Walther, Frank (54. Metallographie-Tagung)

A KPI-based Condition Monitoring System for the Beer Brewing Process - Pasic, Faruk; Wohlers, Benedict; Dziwok, Stefan; Becker, Matthias; Heinrich, Matthias (2019 24th IEEE International Conference on Emerging Technologies and Factory Automation (ETFA))

AuthCheck: Program-state Analysis for Access-control Vulnerabilities - Piskachev, Goran; Petrasch, Tobias; Späth, Johannes; Bodden, Eric (10th Workshop on Tools for Automatic Program Analysis (TAPAS))

Coaching on the Job bei Unternehmen des Maschinen- und Anlagenbaus - Wissenslücken schließen zur Weiterpflege modernisierter IT-Anwendungen - Fazal-Baqaie, Masud; Strüwer, Jan-Niclas; Schmelter, David; Dziwok, Stefan (Projektmanagement und Vorgehensmodelle 2019 (PVM 2019))

Improvement of Software Requirements Quality based on Systems Engineering - Holtmann, Jörg

Component-Based Refinement and Verification of Information-Flow Security Policies for Cyber-Physical Microservice Architectures - Gerking, Christopher; Schubert, David (International Conference on Software Architecture (ICSA 2019))

Application-aware Intrusion Detection: A Systematic Literature Review and Implications for Automotive Systems - Schubert, David; Eikerling, Hendrik; Holtmann, Jörg (17th escar Europe : embedded security in cars)

Monitoring and Control of Production Processes based on Key Performance Indicators for Mechatronic Systems - Wohlers, Benedict; Dziwok, Stefan; Pasic, Faruk; Lipsmeier, Andre; Becker, Matthias (International Journal of Production Economics)
The processes for manufacturing and operating modern technical products require expertise in multiple disciplines like mechanical engineer-ing, electrical engineering, and software engineering. Assessing the current condition and quality of these processes and the machines in-volved is challenging due to the inherent complexity of the products and the required expertise in multiple engineering domains. Globaliza-tion and increasing competition make it necessary to reduce production costs while at the same time ensuring high throughput and product quality. Without the ability to precisely assess the condition and quality of production processes and involved machines, taking action to steer these metrics is nearly impossible and results in unnecessary high production costs. In our previous publications, we introduced the concept of Key Performance Indicators (KPIs) for mechatronic systems as a concept to assess the condition and quality of products and production processes in a graspable yet substantial and efficient way. In this paper, we further refine our KPI concepts und evaluate them for two different use cases: we apply our KPI concept to a manufacturing process in the mechatronic system domain and an operation process in the food production domain. We provide detailed insights in how we applied our concepts within these domains and report about lessons learned. In addition, we provide a business case estimation for our soft-ware solution that assesses the KPIs of our food production domain example.

Designing and Integrating IEC 62443 Compliant Threat Analysis - Fockel, Markus; Merschjohann, Sven; Fazal-Baqaie, Masud; Förder, Torsten; Hausmann, Stefan; Waldeck, Boris (European System, Software & Service Process Improvement & Innovation Conference (EuroSPI 2019))

Assisted setup of forming processes: architecture for the integration of non-adjustable disturbances - Gräler, Manuel; Wallow, Astrid; Henke, Christian; Trächtler, Ansgar (Procedia CIRP)

Decentralized Energy Management for Smart Home System of Systems - Michael, Jan; Henke, Christian; Trächtler, Ansgar (Syscon 2019 - The 13th Annual IEEE International Systems Conference)

Regelung kollaborativer Robotersysteme zur benutzerfreundlichen, flexiblen Fertigung kleiner Losgrößen am Beispiel eines halbautomatischen Schweißvorgangs - Schütz, Stefan; Rüting, Arne Thorsten; Henke, Christian; Trächtler, Ansgar (Fachtagung Mechatronik 2019)

Open-loop linearization for piezoelectric actuator with inverse hysteresis model - Riepold, Markus; Maslo, Semir; Han, Ge; Henke, Christian; Trächtler, Ansgar (Vibroengineering PROCEDIA)

Umsetzung einer echtzeitfähigen modellprädiktiven Trajektorienplanung für eine mehrachsige Hybridkinematik auf einer Industriesteuerung - Rüting, Arne Thorsten; Henke, Christian; Trächtler, Ansgar (at-Automatisierungstechnik)

Codebase-adaptive detection of security-relevant methods - Piskachev, Goran; Do, Lisa Nguyen Quang; Bodden, Eric (Proceedings of the 28th ACM SIGSOFT International Symposium on Software Testing and Analysis)

Was fehlt (bisher) um Apps sicher zu entwickeln? - Prozesse, Werkzeuge und Schulungen für sichere Apps by Design - Altemeier, Katharina; Becker, Matthias; Dziwok, Stefan; Koch, Thorsten; Merschjohann, Sven (Projektmanagement und Vorgehensmodelle 2019 (PVM 2019))

Model-driven development of condition monitoring software - Pasic, Faruk (Proceedings of the 21st ACM/IEEE International Conference on Model Driven Engineering Languages and Systems: Companion Proceedings)

Safety Requirements Engineering for Early SIL Tailoring - Fockel, Markus
Der hohe Grad an Innovation in mechatronischen Systemen führt zu sogenannten Cyber-Physical Systems (CPS). Diese haben eine komplexe Funktionalität und Kommunikation. Wie sicherheitskritisch solche Systeme sind, wird durch sogenannte Sicherheits-Integritätslevel (SIL) kategorisiert, die durch Normen wie der ISO 26262 definiert werden. Ein bestimmter SIL beschreibt nicht nur die Höhe des Gefährdungsrisikos, sondern diktiert auch den erforderlichen Grad an Sorgfalt bei der Entwicklung des Systems. Ein hoher SIL erfordert die Anwendung von Safety-Maßnahmen mit einem hohen Sorgfaltsgrad in allen Phasen der Entwicklung und impliziert daher einen hohen Safety-Aufwand. SIL-Tailoring ist ein Mittel um den Safety-Aufwand zu reduzieren, indem man Subsystemen geringere SILs zuordnet, falls sie von kritischeren Subsystemen getrennt sind oder redundante Safety-Anforderungen erfüllen. Um den nötigen Safety-Aufwand zu planen, sollten Möglichkeiten für SIL-Tailoring so früh wie möglich identifiziert werden - d.h. bereits in der Anforderungsanalyse. Durch die Komplexität von CPS, ist es schwierig valide SIL-Tailorings zu finden. Die Validität von SIL-Tailorings muss durch Analyse von Fehlerpropagierungspfaden geprüft und durch Argumente im Safety Case begründet werden. Der Beitrag dieser Dissertation ist ein systematischer, tool-unterstützter SIL-Tailoring-Prozess, der im Safety Requirements Engineering angewendet wird. Der Prozess nutzt eine modell-basierte, formale Anforderungsspezifikation und stellt einen Katalog von Anforderungsmustern bereit. Basierend auf diesen Anforderungen werden Fehlerpropagierungsmodelle generiert und Subsystemen automatisch SILs zugeordnet. Das minimiert den Sicherheitsanalyseaufwand. Aus den generierten Ergebnissen wird automatisch ein Safety Case mit Argumenten für die SIL-Tailoring-Validität abgeleitet.

Threat Analysis in Practice - Systematically Deriving Security Requirements - Fockel, Markus; Merschjohann, Sven; Fazal-Baqaie, Masud (19th International Conference on Product-Focused Software Process Improvement (PROFES 2018))
With the growing number of incidents, the topic security gains more and more attention across all domains. Organizations realize their lack of state-of-the-art security practices, however, they struggle to improve their software lifecycle in terms of security. In this talk, we introduce the concept of security by design that implements security practices within the whole software lifecycle. Based on our practical experience from industry projects in the regulated industrial automation and unregulated classical IT domain, we explain how to perform a threat analysis and how to integrate it into the software lifecycle.

Towards Preserving Information Flow Security on Architectural Composition of Cyber-Physical Systems - Gerking, Christopher; Schubert, David (European Conference on Software Architecture (ECSA 2018))

Model-Driven STEP Application Protocol Extensions Combined with Feature Modeling Considering Geometrical Information - Koch, Thorsten; Holtmann, Jörg; Lindemann, Timo (Revised Selected Papers of the 5th International Conference on Model-Driven Engineering and Software Development)
Original equipment manufacturers (OEMs) build mechatronic, variant-rich systems using components from several suppliers in industry sectors like automation. The OEMs have to integrate the different components to the overall system based on a virtual layout. For this purpose, the suppliers provide geometrical information via the standardized exchange format STEP. Beyond the geometrical information, the OEMs need additional logical and technical information for the integration task as well as the variant handling. For that reason, STEP provides an extension mechanism for extending and tailoring STEP to project-specific needs. However, extending STEP requires extending several capabilities of all involved tools, which prevents the project-specific utilization of the STEP extensions mechanism. In order to cope with this problem, we presented in previous work a model-driven approach enabling the flexible specification of STEP extensions and particularly the automatic derivation of the required capability extensions for two involved tools. Nevertheless, the OEMs still need to apply several engineering tools from different domains to consider logical as well as geometrical constraints between product variants. In this paper, we hence combine our previous approach with extended feature models that consider conventional logical and particularly geometrical information, thereby enabling a holistic product line engineering for mechatronic systems. By means of an automation production system example, we illustrate how OEMs can orchestrate their overall supply and development processes through the combination of both approaches.

Towards Scenario-based Security Requirements Engineering for Cyber-Physical Systems - Koch, Thorsten (International Workshop on Security for and by Model-Driven Engineering (SecureMDE 2018))

Automated Synthesis of a Real-Time Scheduling for Cyber-Physical Multi-core Systems - Geismann, Johannes; Höttger, Robert; Krawczyk, Lukas; Pohlmann, Uwe; Schmelter, David (Model-Driven Engineering and Software Development)
Cyber-physical Systems are distributed, embedded systems that interact with their physical environment. Typically, these systems consist of several Electronic Control Units using multiple processing cores for the execution. Many systems are applied in safety-critical contexts and have to fulfill hard real-time requirements. The model-driven engineering paradigm enables system developers to consider all requirements in a systematical manner. In the software design phase, they prove the fulfillment of the requirements using model checking. When deploying the software to the executing platform, one important task is to ensure that the runtime scheduling does not violate the verified requirements by neglecting the model checking assumptions. Current model-driven approaches do not consider the problem of deriving feasible execution schedules for embedded multi-core platforms respecting hard real-time requirements. This paper extends the previous work on providing an approach for a semi-automatic synthesis of behavioral models into a deterministic real-time scheduling. We add an approach for the partitioning and mapping development tasks. This extended approach enables the utilization of parallel resources within a single ECU considering the verification assumptions by extending the open tool platform App4mc. We evaluate our approach using an example of a distributed automotive system with hard real-time requirements specified with the MechatronicUML method.

Formal, Model- and Scenario-based Requirement Patterns - Fockel, Markus; Holtmann, Jörg; Koch, Thorsten; Schmelter, David (6th International Conference on Model-Driven Engineering and Software Development (MODELSWARD 2018))
Distributed, software-intensive systems such as automotive electronic control units have to handle various situations employing message-based coordination. The growing complexity of such systems results in an increasing difficulty to achieve a high quality of the systems' requirements specifications. Scenario-based requirements engineering addresses the message-based coordination of such systems and enables, if underpinned with formal modeling languages, automatic analyses for ensuring the quality of requirements specifications. However, formal requirements modeling languages require high expertise of the requirements engineers and many manual iterations until specifications reach high quality. Patterns provide a constructive means for assembling high-quality solutions by applying reusable and established building blocks. Thus, they also gained momentum in requirements documentation. In order to support the requirements engineers in the systematic conception of formal, scenario-based requirements specification models, we hence introduce in this paper a requirement pattern catalog for a requirements modeling language. We illustrate and discuss the application of the requirement patterns with an example of requirements for an automotive electronic control unit.

Improving Quality Control of Mechatronic Systems Using KPI-Based Statistical Process Control - Wohlers, Benedict; Dziwok, Stefan; Schmelter, David; Lorenz, Wadim (Advances in Manufacturing, Production Management and Process Control - AHFE 2018)

Model-driven allocation engineering: specifying and solving constraints based on the example of automotive systems - Pohlmann, Uwe; Hüwe, Marcus (Automated Software Engineering)
Automotive systems provide sophisticated functionality and are controlled by networked electronic control units (ECUs). Nowadays, software engineers use component-based development approaches to develop their software. Moreover, software components have to be allocated to ECUs to be executed. Engineers have to cope with topology-, software-, and timing dependencies and memory-, scheduling-, and routing constraints. Currently, engineers use linear programming to specify allocation constraints manually and to compute a feasible allocation specification automatically. However, encoding the allocation problem as a linear program is a complex and error-prone task. This paper contributes a model-driven, object constraint language based, and graph pattern based allocation engineering approach for reducing the engineering effort and to avoid failures. We validate our approach with an automotive case study. We specify the software component model, the hardware platform model, and the allocation constraint specification with our engineering approach MechatronicUML. Our validation shows that we can specify allocation constraints with less engineering effort and are able to compute feasible allocation specifications automatically.

Rotordynamic instabilities in washing machines - Drüke, Simon; Bicker, Rainer; Schullter, Bernd; Henke, Christian; Trächtler, Ansgar (Proceedings of the 10th International Conference on Rotor Dynamics - IFToMM. Vol. 2. International Conference on Rotor Dynamics - IFToMM)

Assisted setup of forming processes: compensation of initial stochastic disturbances - Gräler, Manuel; Springer, Robert; Henke, Christian; Trächtler, Ansgar; Homberg, Werner (Swedish Production Symposium)

Umsetzung einer echtzeitfähigen Mehrgrößenoptimierung auf einer Industriesteuerung - Rüting, Arne Thorsten; Henke, Christian; Trächtler, Ansgar (EKA 2018 Entwurf komplexer Automatisierungssysteme - Beschreibungsmittel, Methoden, Werkzeuge und Anwendungen)

Model based Setup Assistant for Progressive Tools - Springer, Robert; Graeler, Manuel; Homberg, Werner; Henke, Christian; Trächtler, Ansgar (AIP Conference Proceedings)

Recent Developments in Hardware-in-the-Loop Testing - Millitzer, Jonathan; Mayer, Dirk; Jersch, Torben; Henke, Christian; Michael, Jan; Tamm, Christoph; Ranisch, Christopher (IMAC-XXXVI Conference and Exposition on Structural Dynamics)

Holistic Requirements for Interdisciplinary Development Processes - Lankeit, Christopher; Michael, Jan; Henke, Christian; Trächtler, Ansgar (Proceedings 1st International Workshop on Learning from other Disciplines for Requirements Engineering)

Model-based precision position and force control of SMA actuators with a clamping application - Pai, Arathi; Riepold, Markus; Trächtler, Ansgar (Mechatronics)

Rapid-Control-Prototyping as part of Model-Based Development of Heat Pump Dryers - Holtkötter, Jens; Michael, Jan; Henke, Christian; Trächtler, Ansgar; Bockholt, Marcos; Möhlenkamp, Andreas; Katter, Michael (Procedia Manufacturing)

Systemmodelle als Schlüssel zu durchgängigen XIL-Testszenarien - Schmitz, Joachim; Fockel, Markus (Tag des Systems Engineering 2017)
Intelligente technische Systeme, wie autonom fahrende Fahrzeuge, werden in einem hohen Maß durch Software realisiert. Der Weg zum autonomen Fahren führt unweigerlich über eine steigende Vernetzung von Steuergeräten im Fahrzeug und über Fahrzeuggrenzen hinweg. Damit einher geht eine stetig steigende Komplexität der Software. Deshalb liegt es auf der Hand, dass die systematische Qualitätssicherung für derartige technische Systeme sehr früh, also bereits entwicklungsbegleitend, erfolgen muss. Dazu lässt sich das Software-in-the-Loop-Verfahren einsetzen, das auf etablierte Techniken des Hardware-in-the-Loop-Verfahrens zurückgreift. Eine besondere Herausforderung besteht darin, Simulationsmodelle und Testbibliotheken sowie die zugehörigen Visualisierungs- und Testwerkzeuge in beiden Welten synergetisch zu nutzen. Das Ziel ist eine einheitliche X-in-the-Loop (XIL) Basis für beide Verfahren. Der Schlüssel zu einer einheitlichen Basis für durchgängige XIL-Testszenarien ist der Einsatz eines übergeordneten Systemmodells. Es definiert die Systemgrenze und umliegenden Systeme in der Umwelt. Zudem dient das Systemmodell als Ordnungsschema für die Ablage der Artefakte wie Verhaltensmodelle, Testskripte, Parametersätze oder Workflows. Ein zentrales Datenmanagementwerkzeug, welches sämtliche Strukturinformationen, Verhaltensmodelle und Variantenbezüge verknüpft, ermöglicht ein teilautomatisches Umschalten zwischen den Testszenarien. In diesem Beitrag stellen wir eine solche Lösung vor.

How to Efficiently Build a Front-End Tool for UPPAAL: A Model-Driven Approach - Schivo, Stefano; Yildiz., Bugra M.; Ruijters, Enno; Gerking, Christopher; Kumar, Rajesh; Dziwok, Stefan; Rensink, Arend; Stoelinga, Mariëlle (Dependable Software Engineering, 3rd International Symposium (SETTA 2017))

Model-based Requirement Pattern Catalog - Fockel, Markus; Holtmann, Jörg; Koch, Thorsten; Schmelter, David
Scenario-based requirements engineering addresses the message-based coordination of software-intensive systems and enables, if underpinned with formal languages, automatic requirements validation techniques for improving the quality of a requirements specification. One of such requirements engineering approaches bases on a recent visual Live Sequence Chart variant compliant to the Unified Modeling Language, so-called Modal Sequence Diagrams (MSDs). The usage of patterns is known to be constructive thanks to assembling solutions by means of reusable building blocks that are proven in practice, so that recurring problems do not need to be solved over and over again. Thus, patterns also gained momentum in the area of requirements documentation. In this technical report, we introduce a model- and scenario-based pattern catalog for MSD requirements. Our MSD requirement pattern catalog consolidates and unifies 86 requirement patterns from three well-known, practice-oriented requirement pattern catalogs, each covering different aspects.

Specification and Verification for Real-Time Coordination Protocols of Cyber-physical Systems - Dziwok, Stefan
Cyber-physische Systeme (CPSs) sind die nächste Generation von eingebetteten Systemen, die fortwährend ihre Zusammenarbeit koordinieren, um anspruchsvolle Funktionen zu erfüllen. Die Koordination zwischen ihnen kann in Software mittels asynchroner Nachrichtenkommunikation realisiert werden. Um die funktionale Korrektheit der Software zu gewährleisten, ist aufgrund der Kritikalität dieser Systeme eine formale Verifikation wie z.B. Model Checking notwendig. Die Eingabesprache eines Model Checkers unterstützt jedoch domänenspezifische Aspekte wie asynchrone Kommunikation nicht direkt, wodurch diese vom Softwareingenieur mittels zahlreicher Modellelemente spezifiziert werden müssen. Dies ist hochgradig komplex und somit fehleranfällig. Im Rahmen dieser Arbeit wird eine modellgetriebene Methode zur domänenspezifischen Spezifikation und vollautomatischen Verifikation der nachrichtenbasierten Koordination von CPSs präsentiert. Mit Hilfe dieser Methode kann der Softwareingenieur die Koordination kompakt modellieren und muss nicht länger verstehen, wie seine Spezifikation auf der Ebene des Model Checkers ausgedrückt wird. Insgesamt wird die Komplexität für den Softwareingenieur somit deutlich handhabbarer. Bezüglich der Spezifikation einer solchen Koordination definiert die Arbeit eine domänenspezifische Sprache namens Real-Time Coordination Protocols (RTCPs). Darüber hinaus wird eine domänenspezifische Sprache zur Spezifikation von Verifikationseigenschaften eingeführt und Entwurfsmuster für RTCPs präsentiert, um die Anzahl der Modellierungsfehler zu senken.

Toward Learning Realizable Scenario-based, Formal Requirements Specifications - Schmelter, David; Greenyer, Joel; Holtmann, Jörg (4th International Workshop on Artificial Intelligence for Requirements Engineering (AIRE))
Distributed, software-intensive systems such as fully automated cars have to handle various situations employing message-based coordination. The growing complexity of such systems results in an increasing difficulty to achieve a high quality of the systems’ requirements specifications, particularly w.r.t. the realizability of the specifications. Scenario-based requirements engineering addresses the message-based coordination of such systems and enables, if underpinned with formal languages, automatic requirements validation techniques for proving the realizability of a requirements specification. However, formal requirements modeling languages require a deep knowledge of requirements engineers and typically require many manual iterations until they find a realizable specification. In order to support requirements engineers in the stepwise development of scenario-based requirements specifications, we propose to evolve a high-quality specification from a (presumably unrealizable) manually created specification employing an evolutionary algorithm. In this paper, we show our results on automatically evolving new assumptions on the systems’ environment behavior that guarantee a realizable requirements specification. Based on this contribution, we outline our research roadmap toward our long-term goal of automatically supporting requirements engineers in finding high-quality requirements specifications.

Improving the Product Control of Mechatronic Systems Using Key Performance Indicators - Wohlers, Benedict; Dziwok, Stefan; Bremer, Christian; Schmelter, David; Lorenz, Wadim (Proceedings of the 24th International Conference on Production Research (ICPR))

Reducing the Verbosity of Imperative Model Refinements by using General-Purpose Language Facilities - Gerking, Christopher; Schubert, David; Budde, Ingo (Theory and Practice of Model Transformation, 10th International Conference (ICMT 2017))